Comparison of implicit and explicit motor sequence learning in children with ADHD and their typical peers - Navid Mirzakhany- Araghi; Marzeih k hoshalipanah; Vahid Nejati; Zahra Pashazadeh- Azari; Mehdi Tabatabaee (مجله پژوهش در علوم توانبخشی, 2014)
Introduction: The aim of this study was to assess of both implicit and explicit motor sequence learning in children with attention deficit hyper activity disorder (ADHD) and typical peers , by serial reaction time task.